The effects of ill health and informal care roles on the employment retention of mid-life women: Does the workplace matter? - Austen, Siobhan; Ong, Rachel (Sage Journals, 2013)
This article uses longitudinal data to measure the effects of ill health and informal care roles on the employment chances of mid-life women, and to examine how these effects are mediated by workplace characteristics. We find that women in jobs with lower skills/status encounter the greatest difficulty in finding accommodations for changes in their health and informal care roles. We identify an important role for paid sick leave and holiday leave in boosting employment retention. However, we find that the positive employment effects of permanent contracts do not extend to women experiencing increased informal care roles. Additionally, we do not identify a positive link between employment retention and flexible working time arrangements. However, we do establish a link between a preference for reduced working hours and employment cessation, suggesting that some women experience problems in achieving flexible working hours and that this causes some of them to leave work altogether. We argue that these findings are relevant to the design of policy initiatives aimed at lifting rates of workforce participation as part of the response to population ageing.